2017
DOI: 10.1177/8755123317717053
|View full text |Cite
|
Sign up to set email alerts
|

Musical Parenting and Music Education: Integrating Research and Practice

Abstract: Although teachers work constantly with parents, discussions concerning parental roles in children’s music learning are often left at the margins in music teacher training programs. The aim of this article is to offer a review of musical parenting research from an ecological perspective. Bronfenbrenner’s bioecological theory of human development is used as a lens to examine musical parenting research concerning infants, school-aged children, and adolescents. Issues pertaining to contemporary parenting in the We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
(61 reference statements)
2
9
0
Order By: Relevance
“…Specifically, we found that caregivers involved in artistic activities (visual arts, dance, theater, music) during social restrictions and those with higher levels of education seemed to intentionally influence aspects of the musical home environment by encouraging their children to engage in motor activities to music (dancing and moving to the music), singing to/with the child, and exposing their children to a broad range of musical styles. These findings concur with previous evidence suggesting that factors such as caregivers' own engagement with music and educational level can significantly influence musical parenting/caregiving (Custodero and Johnson-Green, 2003 ; Ilari, 2005 , 2017 ; Hartas, 2011 ; Mehr, 2014 ). Interestingly, our results suggested that caregivers currently engaged in various art-related activities (visual arts, dance, theater, music) were more likely to provide a home environment where musical experiences were nurtured during social distancing.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Specifically, we found that caregivers involved in artistic activities (visual arts, dance, theater, music) during social restrictions and those with higher levels of education seemed to intentionally influence aspects of the musical home environment by encouraging their children to engage in motor activities to music (dancing and moving to the music), singing to/with the child, and exposing their children to a broad range of musical styles. These findings concur with previous evidence suggesting that factors such as caregivers' own engagement with music and educational level can significantly influence musical parenting/caregiving (Custodero and Johnson-Green, 2003 ; Ilari, 2005 , 2017 ; Hartas, 2011 ; Mehr, 2014 ). Interestingly, our results suggested that caregivers currently engaged in various art-related activities (visual arts, dance, theater, music) were more likely to provide a home environment where musical experiences were nurtured during social distancing.…”
Section: Discussionsupporting
confidence: 91%
“…Given the importance of musical activities within family environments and the role of parents/caregivers in early childhood musical experiences, particularly of children under the age of 6 years, we were interested in whether changes in families' dynamics imposed by school closures, social distancing, and mandates of quarantine due to the COVID-19 pandemic affected home music-related behaviors of caregivers and children in Brazil. It is well-established that musical parenting/caregiving of young children is influenced by several factors, including caregivers' previous musical experiences and socioeconomic status, family setting, culture, ethnicity, religion, lifestyle, technologies, among others (Custodero and Johnson-Green, 2003 ; Ilari, 2005 , 2017 ; Hartas, 2011 ; Mehr, 2014 ). Earlier research on musical parenting/caregiving of infants and young children in Brazil revealed significant similarities between musical beliefs and practices of urban middle-class Brazilian caregivers with those of other Western countries (Ilari et al, 2011 ; Ilari and Young, 2016 , p. 104).…”
Section: Introductionmentioning
confidence: 99%
“…Given that the GEM is a rating scale for use by parents, it necessarily entails some degree of subjective judgment on the part of the respondent, e.g., "My child doesn't understand why other people get upset." It is possible that parent responses are influenced by social desirability bias or other confounding factors (Morsbach and Prinz, 2006;Ilari, 2018). However, the original GEM authors found that ratings of children's empathy converged with independent reports of children's prosocial behavior, suggesting that parent reports reflect children's observed behavior with reasonable accuracy.…”
Section: How Many Days Per Week Do You Actively Practice Lesson Matermentioning
confidence: 99%
“…The latter groups were less likely to enrol their children in organised activities and more likely to emphasise, in Lareau’s (2002: 748) terms, the ‘accomplishment of natural growth’. Ilari’s (2013, 2016, 2018) international fieldwork systematically considers the concept of concerted cultivation in relation to music education. Whilst she identifies significant cultural variation, Ilari nonetheless observes that social class continues to exert an influence in musical childhoods across the world, particularly on the extent of parental involvement.…”
Section: Music Education and The Neo-liberal Parentmentioning
confidence: 99%
“…Whilst she identifies significant cultural variation, Ilari nonetheless observes that social class continues to exert an influence in musical childhoods across the world, particularly on the extent of parental involvement. Ilari (2018: 46) proposes the existence of ‘musical parenting’ as ‘a group of music-related cognitions, values, and behaviours of parents in relationship to their children’ with ‘clear implications for music teaching and learning’. Common dispositions include possessing musical instruments at home, the preparedness to purchase further instruments as necessary and a tendency to take children to hear live concerts.…”
Section: Music Education and The Neo-liberal Parentmentioning
confidence: 99%